2015
DOI: 10.1289/ehp.1307711
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Atherosclerosis: A Cross-Sectional Analysis of FourEuropean Cohort Studies in the ESCAPE Study

Abstract: Background:In four European cohorts, we investigated the cross-sectional association between long-term exposure to air pollution and intima-media thickness of the common carotid artery (CIMT), a preclinical marker of atherosclerosis.Methods:Individually assigned levels of nitrogen dioxide, nitrogen oxides, particulate matter ≤ 2.5 μm (PM2.5), absorbance of PM2.5 (PM2.5abs), PM10, PMcoarse, and two indicators of residential proximity to highly trafficked roads were obtained under a standard exposure protocol (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 41 publications
3
39
1
4
Order By: Relevance
“…However, in these studies traffic noise was not measured or included as a separate exposure variable. Although positive associations between particulate air pollution and cIMT have been reported (Tonne et al 2012;Wilker et al 2013), inverse non-significant associations were observed with NO2 or NOx in a study with four European cohorts (Perez et al 2015), which agrees with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in these studies traffic noise was not measured or included as a separate exposure variable. Although positive associations between particulate air pollution and cIMT have been reported (Tonne et al 2012;Wilker et al 2013), inverse non-significant associations were observed with NO2 or NOx in a study with four European cohorts (Perez et al 2015), which agrees with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…These changes, when severe, increase the risk of occlusion that may result in acute atherothrombotic events such as myocardial infarction and stroke (Eikendal et al 2015;O'Leary et al 1999). Although associations between air pollution and cIMT have been investigated (Perez et al 2015;Tonne et al 2012;Wilker et al 2013), we are not aware of studies examining associations between exposure to road traffic noise and cIMT. This association could be on the stress-related pathway between traffic noise exposure and cardiovascular events (Basner et al 2014;Munzel et al 2014) as systolic blood pressure stress reactions, for example, have been linked to progression of cIMT (Jennings et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although all exposure metrics are equally used as a surrogate of personal exposure in epidemiological studies, exposure modeling is strongly influenced by the spatial and temporal variation of exposure and exposure sources [5]. Furthermore, aims, application, input data but also the complexity of models might differ, yielding not only different exposure estimates but consequently different health effect estimates in terms of magnitude and/or statistical significance [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Outra meta-análise realizada por Liu et al, (2015) Cinco outros estudos desta revisão sistemática Lenters et al, 2010;Gan et al, 2014;Perez et al, 2015) referiram-se à relação entre EIMC e proximidade ao tráfego. Devido à expressão de dados diferentes resultados de metodologias distintas, não foi possível realizar meta-análise.…”
Section: A Ultrassonografia De Carótidas Como Método Para Identificaçunclassified
“…Perez et al (2015) concluíram, também, em seu estudo, que morar na proximidade de vias de alto tráfego pode ser positivamente associado às medidas da EIMC. Vários outros estudos recentes observando as associações de EIMC com exposição ao combustível de biomassa descrito por Painschab et al (2013) e a poluição do ar relacionada com o tráfego (Rivera et al, 2013) mostraram resultados estatisticamente significativos.…”
Section: A Ultrassonografia De Carótidas Como Método Para Identificaçunclassified